Imaging the inner structure of a nuclear reactor by cosmic muon radiography. (24th May 2019) - Fujii, Hirofumi; Hara, Kazuhiko; Hashimoto, Shogo; Hayashi, Kohei; Ito, Fumiaki; Kakuno, Hidekazu; Kodama, Hideyo; Nagamine, Kanetada; Sato, Kazuyuki; Satoh, Kotaro; Kim, Shin-Hong; Suzuki, Atsuto; et al.
Abstract: We studied the inner structure of the nuclear reactor of the Japan Atomic Power Company (JAPC) at Tokai, Japan, by muon radiography. Muon detectors were placed outside the reactor building. By detecting cosmic muons penetrating the wall of the reactor building, we could successfully identify objects such as the containment vessel, pressure vessel, and other structures of the reactor. We also observed a concentration of heavy material which can be attributed to the nuclear fuel assemblies stored in the nuclear fuel storage pool.